Privacy-Preserving Security Framework for a Social-Aware Internet of Things - Bernal Bernabe, Jorge; Hernández, Jose Luis; Moreno, M. Victoria; Skarmeta Gomez, Antonio F. (Ubiquitous Computing and Ambient Intelligence. Personalisation and User Adapted Services, 2014)
As smart objects are getting part of our personal space, the new associated services must tackle both, the inherent requirements of IoT and the needs of citizens using such services. Security, trust and privacy concerns are the cornerstone requirements of a social Internet of Things, where users want to share and obtain information in a huge opportunistic environment of connected devices and services. The paper presents an IoT security framework, being devised in the scope of SOCIOTAL EU project, which is based on the Architecture Reference Model (ARM) of IoT-A EU project. The framework extends the traditional ARM putting strong emphasis on security, trust and privacy concerns in order to cope with more opportunistic and secure sharing models required in a social-aware IoT scenarios, where users can set up dynamically communities and bubbles of devices and users.